Christian Martyrdom Never Expires: Some Theological and Ethical Aspects of Obedience usque ad sanguinem - Sławomir Nowosad (The Francis de Sales Scientific Society (TNFS.PL), 2022)
Both in the past and today an act of bearing witness to faith in God through martyrdom has been a unique sign and testimony of love for Christ who himself was obedient to the Father usque ad mortem. It is at the same time a clear judgment against those cultures, which acknowledge odium fidei. In his moral encyclical Veritatis Splendor John Paul II points to several arguments in order to emphasize that the way of martyrdom has lost none of its relevance and significance for Christians nowadays. The Pope's claim is grounded on the fact that "faith possesses a moral content" and so it is false to separate faith (credenda) from moral life (agenda) of those who believe. Consequently, in particular circumstances Christians are called to be ready to lay their lives both for love of God and acceptance of his commandments. Through imitating their Lord usque ad sanguinem his disciples demonstrate and defend their human dignity received from the Creator, the holiness of God's law as well as the holiness of the Church.